Social intelligence in health professions educationists: how it helps to deal with challenges at the workplace? a mixed-method study - Abbasi, Laila Shakeel; Yasmeen, Rahila; Ali, Shabana (Journal of the Pakistan Medical Association, 2024)
Objective: To identify the social intelligence of medical educationists, and the coping strategies used to deal with workplace challenges. Method: The mixed-method study with an explanatory sequential design was conducted from March 15 to July 30, 2021, after approval from the ethics review committee of Riphah International University, Rawalpindi, Pakistan, and comprised medical educationists working in medical and dental colleges and institutions across the country. Data was collected using Tromso social intelligence scale in the quantitative phase. The socially intelligent educationists were identified, and were interviewed. Qualitative data was subjected to thematic analysis to identify predominant themes explaining the coping strategies used. Results: In the quantitative phase, there were 80 participants; 51(63.7%) females and 29(36.3%) males, with 24(30%) having >10 years of professional experience. Of them, 11(13.8%) scored low, 54(67.5%) moderate and 15(18.8%) high on the social intelligence scale. In the qualitative phase, there were 13 subjects; 9(69.2%) females and 4(30.8%) males. There were 4 themes identified as coping strategies; inspire respect and trust, bringing readiness before a change, a collaborative and inclusive approach, and soft skills. Conclusion: Variation was seen in the levels of social intelligence among medical educationists working in academic institutions. Those with high levels of social intelligence used their non-cognitive soft skills to manage workplace challenges. Key Words: Social intelligence, Medical education, Workplace, Coping strategies, Coping skills.